O papel da educação no cuidado com as pessoas egressas dos hospitais psiquiátricos de Sorocaba - Ribeiro, Thais Regina Zamboni (2018)
The present dissertation was based on a field work that had as objective to reflect on the role of education in the care of the people who left the long-stay hospitalizations of the psychiatric hospitals of Sorocaba, considering that some of these former residents of the hospitals returned to the school, in the context of Youth and Adult Education (EJA). After the contextualization of the Psychiatric Reform in Brazil and the specificities of the region of Sorocaba, the Youth and Adult Education Policy is discussed as an inclusive proposal, providing a reflection on education and humanization. The participants of the research were four people who had the experience of the long hospitalizations, residents of the Therapeutic Residences of the city of Sorocaba and that are inserted in the school system, in the EJA modality, besides three teachers, a school coordinator and a psychologist. The qualitative analysis of the narratives showed that the early age interruption of regular studies generated a feeling of sadness and resignation. The EJA, after the deinstitutionalization, in turn, proved to be an opportunity to recover a right that had previously been denied from them. School experiences are permeated by insecurities and fears, because once some stigmas (“the crazy”, “the insane”, “the dangerous person”, "the silly one", “the funny guy”) seemed to stifle the potentialities that could respond to the desires and raise new possibilities of life for these people. The night classes, the fear of passing through the city in an initially unknown territory, the embarrassment of "not knowing" and the feeling of inferiority did not prevent these people from facing the stigma of psychiatric hospitalization and the doubt about their own ability aroused by some teachers. The EJA appeared in the narratives as a place of formation of bonds, affective exchanges, a space of socialization and also as a place to expand the possibilities of the future, because it has given rise to desires for work. It is concluded that the experience of psychosocial rehabilitation should not be focused only in the area of mental health, since many of the conflicts and wishes of these people come from different fields, as in this case, from the education, evidencing the need for the intersectoriality of policies concerning psychiatric deinstitutionalization.